Deskripsi Penerapan Alat Peraga IPA oleh Alumni Program Studi Pendidikan IPA UNM Sebelum dan Sesudah Workshop - Rifda Nur Hikmahwati Arif; Ramlawati Ramlawati; Salma Samputri; Rifda Mardian Arif; Nurfitra Yanto (JKM: Jurnal Kemitraan Masyarakat, 2023)
Teaching aids are one component that determines learning effectiveness. If teachers do not use strategies and utilize teaching aids specifically for science subjects, students will have difficulty capturing and understanding the material provided so that learning objectives are not fully achieved. The use of teaching aids also serves to train students to think more critically and learning will be more interesting because students can see and observe directly the events that occur and their experiences will also increase. However, the development and use of some teaching aids is considered difficult for alumni of science education study programs. This occurs due to the lack of experience and skills of alumni of the science education study program in implementing and making science teaching aids. Therefore, training or workshops are held which aim to improve the quality of learning for partners through workshops (training) in making science teaching aids. The results of the implementation of this activity showed that after a workshop on making teaching aids, the majority of alumni of the science education study program stated that they strongly agreed, while others stated that they agreed to apply teaching aids in the science learning process, whether in physics, biology or chemistry.